Neutron diffraction study of the Pd0.772Ag0.228Dν membrane for hydrogen separation. (9th March 2017) - Catti, M.; Fabelo, O.; Filabozzi, A.; Pietropaolo, A.; Tosti, S.; Pozio, A.; Santucci, A.
Abstract: Experiments of deuterium absorption/desorption were performed on a foil of Pd77 Ag23 (wt%) alloy in the 78–196 °C temperature and 1–4 bar pressure ranges under the neutron beam at ILL (Grenoble). Powder diffraction patterns were collected on the D1B diffractometer ( λ  = 1.2871 Å) on the Pd0.772 Ag0.228 Dν deuterated alloy, and the face-centred-cubic structure was Rietveld-refined locating the D atom in the octahedral site with a variable occupancy ν (=D/M ratio). The results of ν ( T ) curves at different p (D2 ) pressures are discussed in comparison with literature data on H and D absorption into PdAg alloys from thermodynamic measurements. A negative deviation from predictions of Sieverts' law is shown by the dependence of D occupancy on pressure. This effect relates the behaviour of the activity coefficient γ D to D–D and D–M interactions in the solid solution phase. Highlights: Deuterium occupies octahedral sites in the FCC structure of the Pd77 Ag23 alloy. D occupancy decreases with temperature and increases with pressure. D uptake at 1 bar is enhanced by previous sample treatment at higher pressure. Observed deviations from Sieverts' law are ascribed to D–D repulsion in the structure.